KNOWLEDGE OF BULL FIGHTING RAISING A CASE STUDY BAN NAIMONG COMMUNITY PROM LOK SUB-DISTRICT, PROMKIRI DISTRICT, NAKHON SI THAMMARAT PROVINCE - โชติเชย, ฐาปวุฒิ; Damrongwattana, Jittima; Prathum , Boonying; Onchun , Pongprasit; (Kongkawai), Phrakhruwinaithon Suriya Suriyo (Journal of MCU Phetchaburi Review, 2022)
The research of Study Knowledge of Bull Fighting Raising. A Case Study Ban Naimong Community Prom Lok Sub-district, PromKiri District, Nakhon Si Thammarat Province. The purposes of this research were to study Knowledge of Bull Fighting Raising. A Case Study Ban Naimong And study to Guidelines to promote Bull Fighting Raising. A Case Study Ban Naimong Community Prom Lok Sub-district, PromKiri District, Nakhon Si Thammarat Province. by using a qualitative research methodology Interviews with a group of 5 butt cattle breeders and 3 supporters. The Results of the research found that ; 1. Knowledge of Bull Fighting Raising. A Case Study Ban Naimong ; 1.1) Background and development of cows in the southern region Bullfighting is a native sport of the southern people. The first bullfighting was when the cows collided for fun after harvesting the crops from the fields. Currently there will be cattle raising for competition. Betting against each other. 1.2) Selection of cattle breeds The cattle breed must be pure Thai. The breeder is a butt. The offspring that come out will be a stoic bull with a strong heart and a good sense of wit. 1.3) peculiarities body structure selection by choosing a cow with a large breast The slender buttocks sloped down like a lion's structure. color characteristics of cows and the good moral character of the bull Most of them will choose a butt that looks like a butt bull textbook. 4) Raising cattle Raising cows before mating Shepherds must take the cows out for a walk in the morning and in the evening after the exercise walk. twice a day To bathe the buttocks must be meticulously bathed. While taking a shower, the cow-bump nanny touches his body with his hand. to test whether the cow is normal or not When a cow hits a bath and wipes and apply turmeric to keep cows from getting cold after shower Then take the cow to dry in the sun. It will eat grass at the same time. Grass that is popular among the cattle herders include rattan grass and grass rakes. Sun exposure is an activity of the cattle herders that must be done in 1 day. Big will bite and do it in conjunction with feeding. Raising cattle while being in a collision When a partner is caught, they must make a collision contract prepared by the bullfighting field. When the contract is completed The owner of the cow will bring his cow to live in the barn provided by the field. Number of caretakers Usually there are 4-5 people, for some camps there will be 5-6 mentors, depending on the area. which will have to share the duties Supplements must be food that contains minerals and vitamins to strengthen muscles, bones, shiny skin, and beautiful fur. The most popular thing to do while cows are in a fight is to apply honey to the cow's horns after taking a bath. This will make him hard, tough, not brittle or easily broken. 1.5) Bullfighting training selection of sparring partners Choose one that is similar in body structure. Time and place of rehearsal Choose to practice in the morning The amount of time to practice pairs Each rehearsal is not limited to rehearsal time. The first rehearsal started with little time. And next time will increase more and more to suit the physical condition. Placing a cow before getting caught in a collision Choose a pair that has the same body. The height and length of the body are similar. Choose a butt that has a similar horn tip. so that when the bulls are placed, they can fight each other and exercise to the fullest. 2. Guidelines to promote Bull Fighting Raising. A Case Study Ban Naimong Community. 2.1) Funding Promotion Guidelines The buttstocks need funds to raise the buttocks. in the breeding of cattle Bringing in the purchase of equipment building a house Creating a training ground for butt cows, etc. 2.2) Approaches to promote the body of knowledge in raising butt cows. should publicize Technical information about butt cattle raising. 2.3) Guidelines to promote group integration. Establishment of a group of cattle herders is a group to exchange knowledge Exchange of butt-cow breeds 2.4) Approaches to promote management and management There should be a management of the cattle herders. since the start of the party Must study the information on raising well. It is planned to develop the species. Plan for breeding cattle Plan your raising and training sessions so that the buttocks have a healthy body. and always ready for the crash to compete.